Aplicação de métodos hidroacústicos para estudo e dragagem na região portuária de Cabedelo - PB, Brasil - LOPES, Victor Hugo Rocha (Universidade Federal do Pará, 2019)
This paper presents the use of hydroacoustic methods used for mapping and detection of subsurface stratigraphic features to support a project of dredging and demolishing of the left edge of the navigation channel of the Paraíba do Norte's River to expand the port zone of Cabedelo/PB. High-resolution seismic data and bathymetric data are used to map two main objectives: top of the Acoustic Rocky Basement (TARB) and the superimposed sedimentary package. This information is important to support the volume calculation of the material to be dredged and/or demolished along the navigation channel. The data analysis indicates that the expansion of the Cabedelo's Port firstly suggested by the Docas do Paraíba Company to be in the Forte Velho's locality becomes expensive due to the large volume of sedimentary and rocky material to be dredged. Thus, the Lucena region is presented as an alternative to the port expansion since presents lower volume of material to be dredged that reduces substantially the costs and time of execution of the work.